Quality Evaluation of Market Acacia catechu by Fingerprint-Chemical Pattern Recognition - Leilei Gao; Xiaochen Sun; Meng Mei; Fang Wang; Jun Yang; Huasheng Peng; Zhilai Zhan (Journal of Chemistry)
Acacia catechu (L.f.) Willd, a leguminous plant, is included in the 2020 edition of the Chinese Pharmacopoeia and is mainly used to treat eczema, mouth ulcers, diarrhea, bruising, and traumatic hemorrhage. However, there are imported and domestic Acacia catechu samples available in China, and their quality and price are very different, which seriously affects the safety and stability of their clinical application. Importantly, there is no simple and effective method for identifying or classifying grades of Acacia catechu. In this study, 47 batches of commercial Acacia catechu were used for identifying or classifying grades of Acacia catechu using high performance liquid chromatography (HPLC) combined with chemometric analysis. Firstly, gradient elution was adopted with 0.05% phosphoric acid water (A)-methanol (B) as the mobile phase to establish chromatographic conditions. The HPLC chromatograms of 47 batches of Acacia catechu samples were analyzed by the “Similarity Evaluation System for Chromatographic Fingerprint of TCM” software (version 2012A). The common peaks of Acacia catechu were identified to evaluate the similarity. Based on the determination results of fingerprint chromatographic peak area, the quality of the collected Acacia catechu was evaluated by chemometric methods such as CA, PCA, and OPLS-DA. The results showed that the collected Acacia catechu samples were significantly divided into three categories. The first-class samples were all imported Acacia catechu except S9 sample, which was domestic Acacia catechu; the second-class samples were partly domestic Acacia catechu and partly imported Acacia catechu; and the third-class samples were all domestic Acacia catechu. Moreover, OPLS-DA of 47 batches of samples showed that the contents of catechin and the total contents of catechin and epicatechin could be used as key indicators for assessing the quality of Acacia catechu. The developed HPLC fingerprint and quantitative analysis method of multi-indicator components can be used for classification and quality evaluation of market Acacia catechu, which has a significant reference value for developing Acacia catechu grade quality standards.